Strategies to Improve the Targeting of Retinal Cells by Non-Viral Gene Therapy Vectors - Bitoque, Diogo B.; Fernandes, Cláudia F.; Oliveira, Alexandra M. L.; Silva, Gabriela A. (Frontiers in Drug Delivery, 2022)
Retinal diseases lead to severe vision loss and are currently a major cause of vision impairment in industrialized countries. The significant number of genetic defects of the retina underlying these disorders, coupled to the absence of effective treatments, require new therapeutic solutions. Recent gene therapy developments in the field of ophthalmic research reveal the great potential of this approach. In recent years, non-viral vectors have been extensively studied due to their properties such as large gene packaging capacity and low immunogenicity. Hitherto, their development and optimisation for retinal gene therapy have been hindered by their inability to directly target retinal cells. The goal of this review is to summarize the most promising strategies to direct non-viral vectors for retinal cells to avoid off-target effects and promote their specific uptake, gene expression and overall efficiency.